Lipoperoxidation and cyclooxygenases 1 and 2 inhibitory compounds from Iryanthera juruensis - Silva, Dulce Helena Siqueira [UNESP]; Zhang, Yanjun; Santos, Luciana A.; Bolzani, Vanderlan da Silva [UNESP]; Nair, Muraleedharan G. (Amer Chemical Soc, 2007)
Plants from Iryanthera genus have been traditionally used as food supplements by South American Indians. The MeOH extract of leaves of Iryanthera juruensis, one of the plants endemic to the Amazon region and consumed in Brazil, and the hexane extract from its seeds inhibited lipid peroxidation (LPO) and cyclooxygenase (COX-1 and -2)) enzymes in in vitro assays. Further analyses of these extracts yielded 5-deoxyflavones (1-5) from the leaf extract and sargachromenol (6), sargaquinoic acid (7), a novel juruenolic acid (8), omega-arylalkanoic acids (9a-c), and the lignan guaiacin (10) from the seed extract. Compounds 3-5 inhibited LPO by 86%, 77%, and 88% at 10 ppm, respectively, and compounds 6 and 9a-c showed inhibition at 76% and 78% at 100 ppm, respectively. However, compounds 7 and 8 were inactive and lignan 10 exhibited LPO inhibitory activity by 99% at 100 ppm compared to commercial antioxidants butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT), and vitamin E. The flavones 1-5 also inhibited COX-1 and -2 enzymes by 50-65% at 100 ppm. Compound 6 showed high but nonselective inhibition of COX-1 and COX-2 enzymes, when compared to aspirin and Celebrex, a nonsteroidal anti-inflammatory drug (NSAID). Compounds 7 and 10 inhibited COX-1 by 60% and 65% and COX-2 by 37% and 18%, respectively, whereas compounds 8 and 9a-c showed little or no activity against these enzymes.
Keywords: Iryanthera juruensis; Myristicaceae; lipid peroxidation; cyclooxygenase; flavone; tocotrienol; omega-arylalkanoic acids; lignan